1994
DOI: 10.1007/bf01552656
|View full text |Cite
|
Sign up to set email alerts
|

Non-union of a midshaft anterior tibial stress fracture: A frequent complication

Abstract: We report a case of non-union of a midshaft anterior cortex tibial stress fracture and review the literature concerning this pathological entity. This is a relatively rare clinical form of tibial stress fracture which often results in delayed union, non-union or complete fracture. Initial management is as for a conventional stress fracture, associated in some cases, according to certain authors, with pulsing electromagnetic field physiotherapy. If after 4-6 months no sign of union is present, surgical manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Non-operative treatment failed to ensure healing, and excision with bone grafting was required. Several other cases of non-union of tibial shaft lesions diagnosed as stress fractures have been reported [20][21][22]. Mabit et al and Rettig et al reported 2 similar cases in which excision and grafting was successful after failure of nonoperative treatment and electromagnetic stimulation [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Non-operative treatment failed to ensure healing, and excision with bone grafting was required. Several other cases of non-union of tibial shaft lesions diagnosed as stress fractures have been reported [20][21][22]. Mabit et al and Rettig et al reported 2 similar cases in which excision and grafting was successful after failure of nonoperative treatment and electromagnetic stimulation [21,22].…”
Section: Discussionmentioning
confidence: 97%
“…Repeated compression loading is the pathophysiological mechanism involved according to Mabit et al [7]. In contrary Wagner et al [8] showed that the anterior aspect of the midshaft of the tibia is an area under tension than compression.…”
Section: Discussionmentioning
confidence: 99%
“…Green et al ont décrit 6 prises en charge difficiles de fractures « de stress » correspondant à une hyperostose cortico-médullaire médio-diaphysaire antérolatérale tibiale associée à une solution de continuité antérolatérale comme retrouvée dans notre série, avec échec du traitement orthopédique, ayant nécessité la réalisation d'une excision-greffe de la lésion [19]. D'autres fractures « de stress » diaphysaires tibiales de consolidation difficile sont retrouvées dans la littérature [20][21][22]. Mabit [21,22].…”
unclassified
“…D'autres fractures « de stress » diaphysaires tibiales de consolidation difficile sont retrouvées dans la littérature [20][21][22]. Mabit [21,22]. Dans notre série, aucune résection-comblement par autogreffe n'a été réalisée.…”
unclassified